"We Need it the Same Day": A Qualitative Study of Caregivers and Community Members' Perspectives Toward the Use of Point-of-Care Early Infant Diagnosis. (1st July 2020) - Katirayi, Leila; Ochuka, Bernard; Mafaune, Haurovi; Chadambuka, Addmore; Baffour, Theresa; Sacks, Emma
Abstract : Background: Only half of the infants tested for HIV ever receive results, leading to low uptake of treatment and increased mortality and morbidity rates. Point-of-care (POC) nucleic acid diagnostic machines allow for the possibility of same-day results. In Kenya and Zimbabwe, as part of an evaluation comparing standard of care with POC testing for early infant diagnosis, a qualitative substudy was undertaken to understand the acceptability of POC among caregivers of HIV-exposed infants and community members. Setting: Kenya and Zimbabwe. Methods: In Kenya, 74 interviews were conducted with caregivers, and 6 focus group discussions were conducted with male and female community members and elders. In Zimbabwe, we conducted 85 interviews and 8 focus group discussions. Data were collected in 2 rounds: 1 before the introduction of POC platforms and 1 after the platforms had been in use for at least 3 months. Interviews were conducted in local languages, and content analysis and constant comparison were used to identify key themes. Results: Reduced time to receive test results lowered caregiver anxiety about the child's HIV status and allowed families to put children on treatment earlier. Printed POC results were seen by some as more trustworthy than conventional handwritten results, believing this reduced the chance of human error; a few distrusted HIV results were generated too quickly. Community awareness of POC was lower among caregivers of HIV-exposed infants. Conclusion: Caregivers are generally very accepting of receiving POC HIV test results; however, additional sensitization among influential community members about the benefits of POC testing is needed.